Inhibition of autophagy increases apoptosis during re‐warming after cold storage in renal tubular epithelial cells. (29th October 2014) - Jain, Swati; Keys, Daniel; Nydam, Trevor; Plenter, Robert J.; Edelstein, Charles L.; Jani, Alkesh
Summary Prolonged cold storage and re‐warming (CS/REW) of kidneys are risk factors for delayed graft function (DGF). Studies in renal tubular epithelial cells (RTECs) have determined apoptosis and autophagy in models of either cold storage (CS) or re‐warming alone. The effect of both cold storage and re‐warming on apoptosis and autophagy, in RTECS is not known and is relevant to DGF as the kidney is subjected to both CS and re‐warming. We hypothesized that CS/REW of RTECs would induce autophagy that protects against apoptosis. In CS/REW, there was increased autophagic flux of RTECs. Autophagy inhibition using an Atg5 siRNA resulted in increased cleaved caspase‐3 and increased apoptotic cells (on both morphology and annexin V staining) during CS/REW. The effect of autophagy inhibition on necrosis in RTECs is unknown. There were increased necrosis and caspase‐1, a mediator of necrosis, during CS/REW, and the Atg5 siRNA had no effect on necrosis and caspase‐1. In a kidney transplant model, there was an increase in LC3 II, a marker of autophagy, in kidneys transplanted after cold storage. In summary, autophagic flux is increased during CS/REW. Autophagy inhibition resulted in increased cleaved caspase‐3 and increased apoptosis during CS/REW without an effect on necrosis or caspase‐1. In conclusion, autophagy inhibition in RTECs after CS/REW induces apoptotic cell death and may be deleterious as a therapy to decrease DGF.